Impact of Cooperative Societies’ Services on Member’s Livelihoods - Joshi, Chhemanand (INTELLIGENCE Journal of Multidisciplinary Research, 2026)
Cooperative societies are voluntary association of people to meet their socio-economic needs. Efficient cooperative organizations are able to settle many of the economic problems faced by the members. It is crucial to understand the effectiveness of cooperative societies’ services as their objectives. The purpose of this study is to examine the impact of cooperative societies’ services on member’s livelihoods. Saving, credit and shareholding programs have been measured as independent variables and member’s livelihood has been taken as dependent variable. Conveniently selected 477 members of Tilakarnali Saving and Credit Cooperative Society were surveyed using structured five-point Likert scale questionnaire. Correlation and regression analysis has been employed to analyze the data. The findings of this study revealed that there is positive relationship between cooperative societies’ services and member’s livelihoods. Saving and shareholding program have statistically significant positive impact on member’s livelihoods except credit program. Since, the saving programs have a stronger influence on member’s livelihood, is the major concern area for the cooperatives to improve member’s livelihoods. The results of this study will be useful in the field of saving and credit cooperative society to understand and improve their services and member’s livelihood in Nepalese context. Furthermore, it will be helpful for the future studies related to cooperatives sector. This study covers the limited programs i.e., saving, credit, and shareholding. Future researchers can conduct their study focusing on the other cooperative programs effecting member’s livelihoods and the moderating effect of demographic variables like, age, gender, education, occupation and others on member’s livelihoods.